Long lasting symptoms of dyspnea, cough and fatigue after COVID-19 - narrative review of epidemiological studies - Ewa Marciniak; Anna Górniak; Wojciech Hanke (Nofer Institute of Occupational Medicine, 2021)
"Long-COVID" is described as long-term effects of SARS‑ CoV‑2 infection that last >4 weeks after the acutephase of infection. The aim of this narrative reviews to evaluate the frequency of occurrence of 3 symptoms often observed in Long-COVID, i.e., chronic fatigue, shortness of breath and cough, and whether comorbidities such as diabetes and arterial hypertension increase the risk of complications after a history of SARS‑ CoV‑2 infection. The method of narrative review was used in this paper. PubMed (May 31, 2021) search was performed to retrieve articles concerning the occurrence of long COVID-19 chronic fatigue, dyspnoea and chronic cough. Studies in which the observation period was 10%, and in the case of arterial hypertension >40%. The average frequency of diabetes 30 days after discharge from the hospital, in populations with a high incidence of diabetes and hypertension, the incidence of chronic fatigue and cough was higher than in the other analyzed groups. Symptoms of dyspnea were most frequently reported in populations with high rates of diabetes, but at the same time in the average percentage of people with arterial hypertension. Persistent symptoms specific to "Long-COVID" can significantly reduce the ability to perform work. In this situation, check-ups performed before returning to work after long-term leave tape on a new dimension. Med Pr. 2021;72(6):711-20